2016
DOI: 10.1080/01616412.2016.1200306
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes in non-aneurysmal non-perimesencephalic subarachnoid hemorrhage

Abstract: Na-NPM-SAH patients without an identifiable bleeding source on initial angiography might have a more benign short- and long-term prognosis than aneurysmal SAH patients. Our study confirms an important diagnostic advantage of a second arteriography. Still, despite the major concern of an undetected aneurysm, the long-term rebleeding rate was low in this subgroup of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
2
8
0
1
Order By: Relevance
“…Previous studies evaluating the risk of a cerebral aneurysm in developing vasospasm and DCI observed higher likelihood in aneurysmal SAH versus nonaneurysmal SAH (e.g., perimesencephalic SAH) (OR 3.79, p = 0.009) [25]. Our results support this evidence from previous studies as we found that the presence of a cerebral aneurysm was associated with a higher probability of DCI (OR 6.5, p = 0.03), in accordance with what previously published [26]. Moreover, we found that ACOM aneurysm had an additive risk of DCI (OR 9.5, p = 0.026) having the worst disease course compared to other aneurysmal locations.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies evaluating the risk of a cerebral aneurysm in developing vasospasm and DCI observed higher likelihood in aneurysmal SAH versus nonaneurysmal SAH (e.g., perimesencephalic SAH) (OR 3.79, p = 0.009) [25]. Our results support this evidence from previous studies as we found that the presence of a cerebral aneurysm was associated with a higher probability of DCI (OR 6.5, p = 0.03), in accordance with what previously published [26]. Moreover, we found that ACOM aneurysm had an additive risk of DCI (OR 9.5, p = 0.026) having the worst disease course compared to other aneurysmal locations.…”
Section: Discussionsupporting
confidence: 93%
“…Considering SAH-related variables, external CSF drainage was included in the regression analysis, since this has been related to unfavorable outcome in the literature [29,30]. Also, anSAH is generally considered a benign pathology compared to aSAH [31,32], therefore SAH-type was also entered.…”
Section: Methodsmentioning
confidence: 99%
“…Повторное кровоизлияние в стационаре описано лишь у 3 из более чем 1 220 проанализированных в литературе случаев ПМСАК, но убедительно документировано лишь у одной 57-летней больной, получавшей антикоагулянты и антиагреганты по поводу острого коронарного синдрома [16]. При выписке из стационара 99% пациентов имеют результат модифицированной шкалы Рэнкин 0-2 балла [8,[17][18][19][20][21][22][23], что отмечено и в нашей работе.…”
Section: Discussionunclassified